Implementation of The Posyandu Program for Integrated Primary Health Care (ILP) in The Management of Hypertension and Diabetes Mellitus in Tanjungpinang City - Rendy Syafutra; Nur Aslamatturahmah Dwi Putri; Eki Darmawan (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
Hypertension and diabetes mellitus require continuous preventive, promotive, and early detection services at the community level. The Integrated Primary Health Care (ILP) Posyandu Program was implemented to expand primary health services through a life-course approach. This study aimed to analyze the implementation of ILP Posyandu for hypertension and diabetes mellitus management in Tanjungpinang City. A qualitative descriptive approach was used, involving observations, in-depth interviews, and documentation. Informants consisted of DKP2KB officials, primary health center personnel, health workers, Posyandu cadres, and community members. The findings indicate that ILP implementation integrates screening, health education, consultation, recording, and referral services. Policy support and coordination among DKP2KB, primary health centers, cadres, and local community structures support program implementation. However, community participation remains uneven, particularly among adolescents and productive-age adults. Implementation is also constrained by limited health personnel, increased cadre workload, variations in cadre capacity, and physical limitations at several service locations. Strengthening health promotion, community outreach, cadre training, human resources, facilities, coordination, and monitoring is required to improve implementation quality and sustain community-based hypertension and diabetes mellitus services.